The predictors of lower limbs varicose veins among healthcare providers - Aziza M. Salem; Arwa B. Massadeh; Loai Alfarajat; Rami Masa'deh (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Lower limb varicose veins (LLVVs) are a common problem that mostly occurs among healthcare professionals, especially nurses. While the direct cause of LLVVs is not known at present, its predictors have been identified in the literature. The objective of this study is to identify the predictors of LLVVs among nurses in Jordan. MATERIALS AND METHODS: This cross-sectional descriptive study was carried out in Jordan in the period between August 2022 and December 2022. This study was carried out on 407 nurses. The participants were recruited in the study using convenience sampling. LLVVs and predictors were analyzed using binominal logistic regression. The percentage of having LLVVs was 30.7%. RESULT: Results showed that having a family history of LLVVs and older age were significant predictors of developing LLVVs among both male and female nurses. For male nurses, longer shift hours were a significant independent predictor of developing LLVVs, where increased number of deliveries, less sitting time, and increased weight were significant independent predictors of developing LLVVs among female nurses. CONCLUSION: This study highlighted the predictors of LLVVs among nurses, which can be considered in improving the lifestyle and quality of life of nurses in the long term.